2020
DOI: 10.1101/2020.11.25.20238956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on developmental care practices for infants born preterm

Abstract: ObjectivesTo assess the impact of the COVID-19 pandemic on rates of hospital visitation and rates and durations of developmental care practices for infants born preterm delivered by both families and clinical staff.MethodsWe analyzed electronic medical record data from infants born at less than 32 weeks gestational age (GA) cared for in the Lucile Packard Children’s Hospital neonatal intensive care unit (NICU) in a COVID-19-affected period (March 8, 2020 to May 31, 2020) and the analogous period in 2019. Our f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…A smaller study of 231 parents with infants hospitalized in NICUs in the UK and the USA showed that a large percentage (41%) reported to be unable to bond and only 37% were able to be present with their infant as often as desired [10] . Comparisons of the pre- and pandemic status in one NICU clearly link limited parental presence abilities to the COVID-19 pandemic [5] ; and a large global survey of 1120 neonatal care providers, from 62 countries, concluded that restrictions during the pandemic have led to a general separation between the mother-infant dyads [4] , which was also suggested for the entire family [6] . Our results confirm this limited ability to be present with the hospitalized newborn now on a global level and show the magnitude of the impact of implemented restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A smaller study of 231 parents with infants hospitalized in NICUs in the UK and the USA showed that a large percentage (41%) reported to be unable to bond and only 37% were able to be present with their infant as often as desired [10] . Comparisons of the pre- and pandemic status in one NICU clearly link limited parental presence abilities to the COVID-19 pandemic [5] ; and a large global survey of 1120 neonatal care providers, from 62 countries, concluded that restrictions during the pandemic have led to a general separation between the mother-infant dyads [4] , which was also suggested for the entire family [6] . Our results confirm this limited ability to be present with the hospitalized newborn now on a global level and show the magnitude of the impact of implemented restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Together with sick and low birthweight infants, these newborns require specialised care to prevent mortality, support adequate growth and development, and to reduce the risk of morbidities in later life. Yet, their needs have not been considered adequately during the COVID-19 pandemic, which has created exceptional challenges and disrupted healthcare provision across the globe even more [3] , [4] , [5] , [6] . Several measures were put in place to reduce social interaction and the risk for virus transmission, especially in hospital settings including maternity and newborn care units [7] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…inconsistencies due to the ever-changing nature of the hospital care systems. We suspect this to be especially true following the COVID-19 pandemic, in which many units have reallocated staffing to fit hospital-wide demands [45], resulting in reduced consistency of FTE data [46]. This study collected information on the number of approved NICU beds to define NICU size/volume, which does not account for the NICU census.…”
Section: Accepted Manuscriptmentioning
confidence: 99%